A Survey on Cloud Computing and Its Benefits - Abhilasha, Abhilasha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Cloud computing is Internet based development and use of computer technology. It is a style of computing in which dynamically scalable and often virtualized resources are provided as a service over the Internet. Users need not have knowledge of, expertise in, or control over the technology infrastructure "in the cloud" that supports them. Cloud computing is very popular paradigm in the field of computer science where heterogeneous services are delivered to an organization's computer through the Internet. It allows individuals and businesses to access the applications without installation and can access their personal files on any internet connected computer or laptop. Cloud computing means saving and accessing the data over the internet instead of local storage. In this paper, we have conducted a survey on the models of cloud environment, benefits and issues related to it. Â 